Mobility restrictions and mental health among young adults during the COVID-19 pandemic in Ecuador - Tannia Valeria Carpio-Arias; Jefferson Santiago Piedra-Andrade; Tomás Marcelo Nicolalde-Cifuentes; María Victoria Padilla-Samaniego; Estephany Carolina Tapia-Veloz; María Fernanda Vinueza-Veloz (Elsevier, 2022)
Objective: To study the association between mobility restriction and mental health outcomes among Ecuadorian young adults. Method: The present is a cross-sectional study that included a non-probabilistic sample of mostly highly educated young adults. Socio-demographic and mental health data were collected through an online survey, between May and June 2020, when confinement was mandatory in Ecuador. Data on mobility was extracted from Google Community Mobility Reports. Four aspects of the participants' mental health were evaluated: eating behavior (emotional eating), depression, sleep quality and sense of coherence as a proxy of resilience, using previously validated instruments. Data were analyzed using multiple linear regression models in R. Results: Sample included 8426 young adults, with a mean age of 22.85 (standard deviation: 4.43), most of whom were women (n = 5943, 70.53%). During mandatory confinement, in Ecuador mobility in general was reduced by nearly 50% in comparison to January/February, 2020. Less healthy eating behavior, depression, worse sleep quality and lower sense of coherence were associated with higher mobility restriction to workplaces and groceries/pharmacies. Women and youngsters more often showed depression, less healthy eating behavior, worse quality of sleep and lower sense of coherence in comparison with men and older respondents. Conclusions: Mobility restrictions during COVID-19 pandemic were associated with worse self-reported mental health in a sample of young highly-educated Ecuadorian adults. Women and youngsters were the most affected. Our findings highlight the need of implementing health promotion measures directed to ameliorate the effects of confinement on mental health, focusing on women and youngsters. Resumen: Objetivo: Estudiar la asociación entre la restricción de movilidad y la salud mental en personas adultas jóvenes de Ecuador. Método: Estudio transversal que incluyó una muestra no probabilística de personas adultas jóvenes con alto nivel de educación. Los datos sociodemográficos y de salud mental se recolectaron entre mayo y junio de 2020, cuando el confinamiento fue obligatorio, usando una encuesta en línea. Los datos sobre movilidad se extrajeron de Google Community Mobility Reports. Se evaluaron cuatro aspectos de la salud mental: alimentación emocional, depresión, calidad de sueño y sentido de coherencia como proxy de resiliencia, usando instrumentos previamente validados. Los datos se analizaron con modelos de regresión lineal múltiple usando R. Resultados: La muestra incluyó 8426 jóvenes, con una edad media de 22,85 años (desviación estándar: 4.43), mujeres en su mayoría (n = 5943, 70.53%). Durante el confinamiento obligatorio, la movilidad se redujo aproximadamente un 50%. Comportamientos alimentarios menos saludables, depresión, peor calidad del sueño y menor sentido de coherencia se asociaron con mayor restricción de movilidad a lugares de trabajo y pequeños comercios o farmacias. Mujeres y jóvenes mostraron con mayor frecuencia depresión, conductas alimentarias menos saludables, peor calidad del sueño y menor sentido de coherencia. Conclusiones: Las restricciones de movilidad durante la pandemia de COVID-19 se asociaron con una peor salud mental en personas adultas jóvenes con alto nivel de educación. Mujeres y jóvenes fueron los más afectados. Es necesario implementar medidas de promoción de la salud dirigidas a paliar los efectos del confinamiento en la salud mental, especialmente en mujeres y jóvenes.